Ekologiczne koszty zewnętrzne energetyki odnawialnej - Graczyk, Andrzej (Ecological External Costs of Renewable Energy, 2009)
The aim of the article is the qualification of size and the meaning of ecological external costs of renewable energy. Political and legal mechanisms motivating renewable energy development in the European Union and in Poland are briefly presented in the first part. Secondly, there is discussed the evaluation of renewable energy costs in comparison with external costs characteristic for typical Polish technology of energy production. Decision situations for conventional energy producers who can redirect their production on renewable carriers are presented against this background in theoretical perspective
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 154-165